Translating Hopkins’ Young Adult Novel “Mates, Dates, And Chocolate Cheats” into Indonesian: A Design and Development Approach - Rayyana Harifantika; Siti Rohani; Alvin Nouval (Jurnal Linguistik Terapan, 2021)
Novel is well-known as one of the narrative structure literature works. Novel is an invented prose narrative of significant length and complexity that deals imaginatively with human experience, usually through a connected sequence of events involving a group of persons in a specific setting. Teen novel or young adult literature is initially defined as written for readers from 12 to 18 years of age. The genres available in young adult fiction are expansive and include most of those found in adult fiction. Common themes related to young adult fiction include friendship, first love, relationships, and identity. In this research, the researcher chose one of the famous young adult novels series the Mates, Dates series by famous young adult or teen novels author Cathy Hopkins. The current research was aimed to translate Hopkins’ Mates, Dates, and Chocolate Cheats into Indonesian. Following the procedure (a) analysis, (b) design, (c) development, (4) expert validation, and (e) evaluation, the writer translates the novel into in an interesting and easy to understand Indonesia novel for the teenagers. The instruments used for expert validation and evaluation were online questionnaires. The result of the expert validations and evaluation shows that this translation is a good translation in Indonesian.